A Paradox for the Existence Predicate - Meixner, Uwe (Bulletin of the Section of Logic, 2022)
In this paper, a paradox is shown to arise in the context of classical logic from prima facie highly plausible assumptions for the existence predicate as applied to definite descriptions. There are several possibilities to evade the paradox; all involve modifications in the principles of first-order logic with identity, existence, and definite descriptions; some stay within classical logic, others leave it. The merits of the various "ways out" are compared. The most attractive "way out," it is argued, stays within classical logic, except for the fact that it involves a new logical truth: "There is at least one non-existent object." But this "exit" will certainly not be to everyone's taste and liking. Thus, the paradox defies complete resolution (as every good paradox should).